Pengukuran Resiko Teknologi Informasi dengan Pendekatan FRAP: Studi Kasus Pada PT Cowell Development, Tbk - Widjaya, Iwan Kurniawan (ComTech: Computer, Mathematics and Engineering Applications, 2012)
The article purposes are to analyze, identify, and measure the risks found in the use of information technology. The research method used are literature study and field study upon observations, interviews, documentation, and FRAP (facilitated Risk Analysis Process) approach to measure the risk of information technology. The results found are positive and negative findings in the use of information technology. The exixting weaknesses allow the potential risks that may occur. The conclusion is there are vulnerabilities found in the use of information technology that need several recommendations on those risks to improve performance andguarantee data protection and information from any risk arise.